1969
DOI: 10.1002/macp.1969.021280130
|View full text |Cite
|
Sign up to set email alerts
|

N‐äthyl‐pyridinium‐chlorid als lösungsmittel und reaktionsmedium für cellulose

Abstract: I m Rahmen von Versuchen zur homogenen Herstellung von Cellulosederivaten haben wir die Schmelze von N-Athyl-pyridinium-chlorid mit Zusatzen von Pyridin und anderen den Schmelzpunkt erniedrigenden Substanzenl) auf ihre Eignung als Losungsmittel und Reaktionsmedium untersucht. Dabei erhielten wir folgende Resultate : Losefahigkeit des N-Athyl-pyridiniurn-chloridsN-Athyl-pyridinium-chlorid, das sehr hygroskopisch ist, schmilzt bei 118-120°C. Durch Zugabe von maximal 5 0 % Pyridin laBt sich der Schmelzpunkt auf c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 2 publications
0
18
0
1
Order By: Relevance
“…Quantitative acylation is evident from the disappearance of any hydroxyl group absorption at about 3 300 cm -1 along with the increased intensity of ester carbonyl absorption at 1 750 cm -1 shown in the FTIR spectra. From the 1 …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Quantitative acylation is evident from the disappearance of any hydroxyl group absorption at about 3 300 cm -1 along with the increased intensity of ester carbonyl absorption at 1 750 cm -1 shown in the FTIR spectra. From the 1 …”
Section: Resultsmentioning
confidence: 98%
“…Moreover, a minimal chain degradation and high yield due to small consumption of reagent by side reactions may be realized. A variety of homogeneous reactions including acetylation had been performed many years ago in melts of N-ethylpyridinium chloride 1) . Mixtures composed of diethylamine, SO 2 , and dipolar aprotic liquids like dimethyl sulfoxide (DMSO) were used successfully for etherification 2) .…”
Section: Introductionmentioning
confidence: 99%
“…In 1934, Graenacher reported that cellulose dissolved in a mixture of 1-ethylpyridinium chloride and nitrogencontaining base when heated at the melting point (T m ) above 120 C. 21 Moreover, T m was lowered to 77 C by mixing 1-ethylpyridinium chloride with 50% DMF or DMSO. 22 These solvent systems were not typical examples of IL-based solvents because of their relatively high T m and the volatility of the co-solvents. Rogers et al first demonstrated that some ILs could solubilize cellulose, in 2002.…”
Section: ç Cellulose Dissolution With Ionic Liquidsmentioning
confidence: 99%
“…The use of Nethylpyridiniumchloride was first suggested as a solvent for cellulose by CIBA [11]. Husemann and Siefert [12] used a melt of N-ethylpyridiniumchloride for homogenous reactions of cellulose in solution.…”
Section: Resultsmentioning
confidence: 99%